2020
DOI: 10.1186/s12871-020-00990-3
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Antipyretic Analgesics administration intravenously for Preventing Rocuronium-Associated Pain/Withdrawal Response: a systematic review and meta-analysis

Abstract: Background: Rocuronium-associated injection pain/withdrawal response (RAIPWR) was non-ideal but occurred frequently when injection intravenously during anesthesia induction. Many studies had reported that pretreating with antipyretic analgesics (AAs) could reduce the occurrence of RAIPWR, but there was no consensus yet. Therefore, this meta-analysis was designed to systematically evaluate the benefits of AAs on RAIPWR in patients. Methods: PubMed, Cochrane Library, Ovid, EMbase, Chinese National Knowledge Infr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This observation is consistent with those reported by previous studies. [ 3 4 5 ] This study showed that the severity of pain assessed with NRS and opioid consumption in patients with PIP or RIWM were significantly higher than in patients without PIP or RIWM. Our finding suggests that preoperative pain perception may be used to predict pain outcomes after surgery.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This observation is consistent with those reported by previous studies. [ 3 4 5 ] This study showed that the severity of pain assessed with NRS and opioid consumption in patients with PIP or RIWM were significantly higher than in patients without PIP or RIWM. Our finding suggests that preoperative pain perception may be used to predict pain outcomes after surgery.…”
Section: Discussionmentioning
confidence: 77%
“…Propofol and rocuronium, used for induction of general anaesthesia, are often associated with pain (in 25%–100% of patients receiving propofol) or withdrawal movement (in 22%–84% of patients receiving rocuronium). [ 2 3 ] The characteristics of pain associated with propofol and rocuronium are inconsistent. One study reported that the characteristics of pain associated with the two anaesthetic agents are similar in regard to pain during administration, a short duration of pain and a decrease in pain intensity with subsequent injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pain can immediately cause withdrawal movements of the arm and hand and may soon extend to the whole body. 5 This type of body movement reactions can lead to increased incidence of pulmonary aspiration in unconscious patients, detachment or displacement of venous catheters, or other emergencies. Therefore, reducing pain caused by rocuronium injection has important consequences in clinical application.…”
Section: Introductionmentioning
confidence: 99%
“… 6 In addition to drug prophylaxis, studies have shown that the dilution of rocuronium to a lower concentration can also reduce the incidence of injection pain. 5 However, the use of lidocaine alone or of low concentrations of rocuronium alone cannot completely prevent injection pain. Many randomized controlled trials in adults have shown that a variety of opioids, such as fentanyl and sufentanil, can effectively reduce the incidence and severity of pain or muscular fasciculations caused by injection of rocuronium.…”
Section: Introductionmentioning
confidence: 99%